PERSISTENT PAIN IN INTENSIVE CARE SURVIVORS: A SYSTEMATIC REVIEW - Ma’bud, Tasia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Practical evaluation and management of pain are essential due to their potential impact on daily functioning. Pain can be classified into nociceptive, neuropathic, mixed, or idiopathic origins. Critically ill patients are at risk of experiencing long-term complications. Aim: The goal of this study is to find about persistent pain in intensive care survivors. Methods: The study uses the PRISMA 2020 recommendations, 2013–2023, and online reference sources for accuracy and relevance. Result: A total of 659 articles were obtained from PubMed and 276 from SagePub. In 2013, 22 papers were retrieved from PubMed and SagePub. Six articles fulfilled the research criteria. Conclusion: This study agrees with previous research on the prevalence of pain afterward becoming in the ICU.